Enterprise Risk Management Program Quality: Determinants, Value Relevance, and the Financial Crisis1. (16th April 2013) - Baxter, Ryan; Bedard, Jean C.; Hoitash, Rani; Yezegel, Ari
<x xml:space="preserve">Abstract</x> This paper investigates factors associated with high‐quality Enterprise Risk Management (ERM) programs in financial services firms, and whether ERM quality enhances performance and signals credibility to the financial markets. ERM, developed with the assistance of the accounting profession, provides a framework and plan to integrate management of all sources of risk. Challenged by measurement difficulties common to research on management control systems, prior ERM studies present mixed findings. Using ERM quality ratings of financial companies by Standard & Poor's, we find that higher ERM quality is associated with greater complexity, less resource constraint, and better corporate governance. Controlling for such characteristics, we find that higher ERM quality is associated with improved accounting performance. Results show a market reaction to signals of enhanced management control from initial ERM quality ratings and rating revisions, and a stronger response to earnings surprises for firms with higher ERM quality. Focusing on the recent global financial crisis, our analysis suggests that there is no relation between ERM quality and market performance prior to and during the market collapse. However, returns of higher ERM quality companies are higher during the market rebound. Overall, results reveal that firm performance and value are enhanced by high‐quality controls that integrate risk management efforts across the firm, enabling better oversight of managers' risk‐taking behavior and aligning that behavior with the strategic direction of the company.